Different tactics of single-stent endovascular treatment among coronary heart disease patients with coronary artery bifurcation lesions - Z. Kh. Shugushev; Yu. V. Tarichko; Yu. A. Vasyuk (Кардиоваскулярная терапия и профилактика, 2012)
Aim. To analyze the results of different tactics of single-stent endovascular treatment among patients with coronary heart disease (CHD) and coronary artery bifurcation lesions (CABL). Material and methods. The study included 135 CHD patients with CABL. All participants were divided into 2 groups: Group I (n=77; 58,3 %) consisted of patients who underwent coronary artery (CA) main branch (MB) stenting and subsequent kissing balloon angioplasty of a CA side branch (SB). Group II (n=55) included patients with “genuine” CABL, who underwent only MB stenting with SB protection, but without SB balloon angioplasty. Results. In all 132 CABL patients, drug-eluting stents were successfully implanted, with technical effectiveness of 100 % and in-hospital survival of 100 %. Clinical outcomes were similar in both groups, with no major cardiovascular events registered. At the same time, such an important angiographic index as SB diameter was significantly higher in Group I, compared to Group II. At later stages, Group II patients required SB angioplasty and demonstrated habitual angina symptoms, ischemic electrocardiographic (ECG) changes, and slow SB blood flow (TIMI grade <III) after CA MB stenting. Conclusion. MB stenting of CA bifurcation without SB kissing balloon angioplasty cannot be recommended to all CABL patients. Development of habitual angina symptoms, ischemic ECG changes, and slow SB blood flow (TIMI grade <III) often requires subsequent SB kissing balloon angioplasty.